"Natural que seja assim": uma proposta de rede construcional das construções semi-insubordinadas do português brasileiro - Coimbra, Eder Cavalcanti (2022)
Semi-insubordinate constructions (SIC) are reported by Van Linden and Van de Velde (2014) as constructions formed by an initial constituent followed by a noun clause introduced by the connective ‘that’. The initial constituent acts at the level of a matrix clause and expresses an attitudinal assessment of the speaker about the propositional content of the noun clause. This dissertation presents a characterization of the forms and meanings of Brazilian Portuguese semi-insubordinate constructions (BP-SIC) and a proposal for a constructional network of these constructions, based on the analysis of corpus data. Supported by the theoretical assumptions of the Construction Grammar that constructions are conventionalized pairings of form and meaning and that syntactic structures carry meaning themselves, the present analysis seeks to confirm the hypothesis that the BP-SIC belong to a hierarchical network of semi-insubordination and share the abstract form of a schematic syntactic construction, [[X] [que] [finite noun clause]], as well as its evaluative meaning. The [X] component represents the construction’s matrix, an open slot to be filled with an evaluative adjective, noun, adverb or interjection. The connective que has its position fixed and introduces the other open slot of the clause, to be filled by any finite noun clause, carrying the evaluated content. Data collection was carried out in the Web/Dialects set of the Corpus do Português (DAVIES, 2016), a written, synchronic, morphologically annotated corpus, composed of texts from 21st century internet pages, whose portion of the Brazilian variety contains more than half a billion words. The constructions were located in the corpus via search expressions with tags of adjectives, nouns and adverbs in the initial position of the sentence (matrix position), followed by the word que. The attested combinations of form and meaning were tabled, giving rise to the groupings of the constructional network (sub-schemes). 175 types of BP-SIC were verified, counting on their different adjectival, adverbial, noun or (secondary) interjective matrices, with emphasis on adjectivals (117). Most of the matrices express non-modal evaluation, with some mirative uses and emphatic negations. Among the modal evaluation matrices, epistemic, deontic and evidential meanings are expressed.